Measuring patient satisfaction based on a cross-cultural adaptation of ACTA questionnaire: a cross-sectional study - Tarman, Krisnawati; Widayati, Retno; Kusdhany, Lindawati; Hassan, Wan Nurazreena Wan (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACT Introduction: Patient satisfaction after orthodontic treatment is influenced by several factors. Variables such as gender, age, duration of treatment, compliance, and dentofacial improvement also contribute to the level of satisfaction. The aim of this study was to measure patients’ satisfaction with their orthodontic treatment using ACTA Questionnaire at the Orthodontic Clinic, Dental Hospital Faculty of Dentistry Universitas Indonesia. Methods: A cross sectional study to measure patient satisfaction. A validated patient satisfaction questionnaire consisting of five domains and 34 items, was used. The questionnaire was distributed to all patients who met the inclusion criteria via WhatsApp. This study included 120 respondents (93 females and 27 males). Results: The internal consistency of the total scale and the five domains was satisfactory.  Respondents were most satisfied with Domain 1, which concerned the doctor-patient relationship and were least satisfied with domain 5, which addressed situational aspects. Patient satisfaction reflects the quality of health services. In this study, 51.6% of female respondents were satisfied with the treatment, but there were no significant differences between genders. Conclusion: The doctor-patient relationship remains the most important factor contributing to patient satisfaction. Age, gender, education level and socioeconomic status did not influence patient satisfaction. . KEY WORDS: patient satisfaction, cross-cultural adaptation, ACTA questionnaire, risk factors, socioeconomic.Kepuasan pasien diukur menggunakan adaptasi lintas budaya kuesioner ACTA: Studi cross-sectionalABSTRAK Pendahuluan: Kepuasan pasien setelah perawatan ortodonti dipengaruhi oleh beberapa faktor. Faktor-faktor seperti jenis kelamin, usia, durasi pengobatan, kepatuhan, dan perbaikan dentofasial juga terlihat berkontribusi pada tingkat kepuasan. Tujuan dari penelitian ini adalah untuk mengukur kepuasan pasien terhadap perawatan ortodontik menggunakan ACTA Questionnaire di Klinik Ortodontik Rumah Sakit Gigi Fakultas Kedokteran Gigi Universitas Indonesia. Metode: Untuk mengukur kepuasan pasien, digunakan kuesioner yang divalidasi tentang kepuasan pasien yang terdiri dari 5 domain dan 34 items. Kuesioner dikirim ke semua pasien yang sesuai dengan kriteria inklusi melalui WhatsApp. Penelitian ini melibatkan 120 responden, yang terdiri dari 93 perempuan dan 27 laki-laki. Hasil: Konsistensi internal dari skala total dan 5 domain memuaskan.  Responden paling puas dalam domain 1 mengenai hubungan dokter-pasien dan paling tidak puas dalam domain 5 pada aspek situasional. Kepuasan pasien adalah hasil dari pelayanan kesehatan yang baik. Dalam penelitian ini 51,6% responden perempuan puas dengan perawatan ortodonti, tetapi tidak ada perbedaan yang signifikan antara jenis kelamin. Simpulan: Hubungan dokter-pasien tetap menjadi faktor terpenting yang berkontribusi pada kepuasan pasien. Usia, jenis kelamin, pendidikan dan faktor sosial-ekonomi tidak mempengaruhi kepuasan pasien.KATA KUNCI: kepuasan pasien, adaptasi lintas budaya, kuesioner ACTA, faktor resiko, sosio-ekonomi